Late diagnosis of Duchenne's muscular dystrophy presenting as global developmental delay. Issue 7303 (7th July 2001) - Essex, Charles; Roper, Helen
Abstract : Many boys with Duchenne's muscular dystrophy present with global developmental delay before specific motor disabilities are noticed